﻿Monitoring the change in the quality of life of patients with post-COVID syndrome by influence on their functional status - Maria Stamova Vakrilova Becheva; Angelina Georgieva Kirkova-Bogdanova; Petar Jordanov Atanasov; Mariya Sevdelinova Chaneva; Daniela Ivova Taneva; Stefka Achkova Ivanova (Pensoft Publishers, 2023)
Coronavirus disease 2019 (COVID-19) is still a major medical concern. Patients who have recovered from the infection from COVID-19 face the ordeal of post-covid syndrome. In these patients, there is a decrease in physical abilities, in particular musculoskeletal complications and post-traumatic stress, depression and chronic fatigue, which impair their quality of life. This necessitates long-term rehabilitation, which supports recovery after hospitalization. Treatment through movement is part of the rehabilitation measures contributing to the functional recovery of patients with post-covid syndrome. To study how the functional capabilities of these patients improve and how their quality of life is affected, we created a set of physical exercises to be performed at home for 6 months. At baseline and at the end of the study, patients completed the SF-36 quality of life questionnaire. The aim of the study was to track the changes in the quality of life of patients with post-covid syndrome by influencing their functional state. Our study found a decline in the quality of life of the examined patients. After the application of the kinesitherapy program, the functional status of the patients improved, their functional independence was optimized, which contributed to the improvement of the quality of life of the post-covid patients syndrome.